A Household Level Analysis of the Pakistan–Malaysia Free Trade Agreement. (November 2018) - Khan, Muhammad Aamir; Mehmood, Qaisar; Zakaria, Muhammad; Husnain, Muhammad Iftikhar ul
Pakistan and Malaysia have a significant bilateral economic relationship. The Pakistan–Malaysia Free Trade Agreement (FTA) was signed in 2007, and was implemented in 2008. Pakistan's volatile exports to Malaysia never achieved a sustainable period of growth. Trade balance has not achieved significant changes even after 9 years of implementation of the agreement. With this backdrop, this study first quantifies the current FTA between Pakistan and Malaysia and then suggests changes that could be made to improve the outcome for Pakistan. A new global economic trade model is adapted to include more detailed information on Pakistan's labor and household groups into the Global Trade Analysis Project (GTAP) database. This allows for a more detailed analysis of the impact of the FTA on Pakistan at the household level. The results show that there is win–win scenario for both Pakistan and Malaysia if both are able to renegotiate the current FTA to get the same tariff concession as awarded to each other's trading partners.